Parent Questionnaires in Screening for Developmental Language Disorder Among Bilingual Children in Speech and Language Clinics - Abutbul-Oz, Hadar; Armon-Lotem, Sharon (Frontiers in Education, 2022)
Screening for Developmental Language Disorder (DLD) among bilingual children in Speech and Language Clinics is challenged by the use of Societal Language (SL) monolingual norms and by the absence of knowledge about children’s performance in the Home Language (HL) leading to over diagnosis of DLD among bilingual children. The current study examined how bilingual parents’ questionnaire can contribute to a more accurate clinical protocol that can help mitigate the diagnosis difficulties and help disentangle the impact of bilingualism from DLD. Parents of 75 bilingual children (ages 48-82 months) participated in this study. 46 children were referred to Speech and Language Pathologists (SLPs) due to language performance difficulties (Clinically Referred- CR) and 29 were never referred to a SLP (Non-referred- NR). Of the CR group only 19 were diagnosed by the SLP with DLD using dynamic assessment (CR-DLD), while 27 were diagnosed as having typical language development (CR-TLD). Parents of all children filled a Bilingual Parent Questionnaire (BIPAQ, 2012), developed from a SLP's perspective, ith information in five domains: (a) Demographic Information, (b) Developmental background, (c) HL abilities, (d) SL abilities, and (e) Quantity and quality of exposure to both HL & SL. Significantly lower scores were observed for the CR-DLD group compared to the other groups on Developmental background, HL abilities, and SL abilities as well as on the total score. Sentence complexity, difference from other children in language development, and family history significantly distinguished between the CR-DLD and CR-TLD groups. Sentence complexity, difference from other children in language development, and confidence speaking freely distinguished between CR-DLD and NR children. No significant difference was observed between CR-TLD and NR children. A comparison of the CR- DLD and the CR-TLD bilinguals using a ROC curve analysis yielded good sensitivity and specificity, as well as good accuracy (AUC = .869). Our findings show that parent questionnaires can be a valuable part of diagnosis protocol and provide missing information needed for more accurate diagnosis before treatment commences, allowing clinicians alternative options of treatment as well as reducing caseloads at clinics.